2012
DOI: 10.3390/molecules171011978
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Affinity and Molecular Basis of the Structure-Binding Relationship between Urinary Tamm-Horsfall Glycoprotein and Tumor Necrosis Factor-α

Abstract: In a previous study we noted significant THP binding to TNF-α, but did not explore the molecular basis of the structure-binding relationship. In this study, we used lectin-binding ELISA to assess the carbohydrate compositions of THP, BSA, IgG, TNF-α, and IFN-γ. We identified β(1,4)-N-acetylglucosamine oligomers (GlcNAc) and GlcNAc/branched mannose in BSA, IgG, TNF-α, and THP, but not in IFN-γ. These carbohydrate moieties mediated binding with THP. Small amounts of Siaα(2,3)Gal/ GalNAc, Sia(2,6)Gal/GalNAc, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Wu et al [ 61 ] indicated that the intact protein core structure of THP is essential for this protein’s binding with other proteins and immune cells. The same group measured the binding affinity ( K d ) between THP and TNF-α by Scatchard plot analysis and revealed that the binding affinity of THP and TNF-α was 1.4–1.7 × 10 −6 M, which is lower than the antigen–antibody or ligand–receptor binding affinity [ 62 ]. They also identified that β(1,4)- N -acetylglucosamine oligomer (GluNAc) and GluNAc/branched mannose in bovine serum albumin, IgG, and TNF-α are essential for binding with THP.…”
Section: Physiological Functions Of Thpmentioning
confidence: 99%
“…Wu et al [ 61 ] indicated that the intact protein core structure of THP is essential for this protein’s binding with other proteins and immune cells. The same group measured the binding affinity ( K d ) between THP and TNF-α by Scatchard plot analysis and revealed that the binding affinity of THP and TNF-α was 1.4–1.7 × 10 −6 M, which is lower than the antigen–antibody or ligand–receptor binding affinity [ 62 ]. They also identified that β(1,4)- N -acetylglucosamine oligomer (GluNAc) and GluNAc/branched mannose in bovine serum albumin, IgG, and TNF-α are essential for binding with THP.…”
Section: Physiological Functions Of Thpmentioning
confidence: 99%
“…The precise function of this protein is not well understood but is thought to be important for kidney and renal function , and is annotated as exosomal. Glycosylation on this protein has been shown to control protein recognition between THP/uromodulin and other clinically relevant proteins . THP glycosylation also functions in cellular recognition and has been shown to modulate immune cell activation. , Additionally, this protein also blocks against infection through the effective “coating” of pathogens’ surfaces, thus preventing renal infections .…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsic binding affinity between the fluorescence-labeled IgD antibody and IgD on IgDR in CD4 + T cells was evaluated by fluorescence-based receptor binding assays ( Wu et al, 2012 ; McCall et al, 2014 ). IgD binding for detection by flow cytometry was performed as follows.…”
Section: Methodsmentioning
confidence: 99%